2019
DOI: 10.21475/ajcs.19.13.06.p1614
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of liming on chemical attributes of tropical sandy soil and soybean (Glycine max L.) yield

Abstract: Lime application is the most appropriate technique to raise soil pH, decrease Al3+ toxicity and increase Ca2+ and Mg2+ contents in acidic tropical and subtropical moist soils. The objective of this research is to evaluate changes in chemical attributes and soybean yield in sandy soil after lime incorporation. The soil was classified as a typical Quartzipsamments cultivated with (Brachiaria decumbens Stapf) pasture, and its degradation state was classified as strong. The experimental design was a randomized blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The rate of reaction of a lime material with soil and the maximum pH increase depends on several factors, including initial soil pH, application rate, OM, and clay content (Costa et al, 2016). Alleoni et al (2005), andNeto et al (2019) reported fast lime reaction in the soil to a depth of 20 cm under NT. Therefore, the high pH increase observed up to 20-cm depth was proportional to the application rate and reaction time of lime agree with published results.…”
Section: Soil Acidity Indicators For No-tillage Sitesmentioning
confidence: 99%
“…The rate of reaction of a lime material with soil and the maximum pH increase depends on several factors, including initial soil pH, application rate, OM, and clay content (Costa et al, 2016). Alleoni et al (2005), andNeto et al (2019) reported fast lime reaction in the soil to a depth of 20 cm under NT. Therefore, the high pH increase observed up to 20-cm depth was proportional to the application rate and reaction time of lime agree with published results.…”
Section: Soil Acidity Indicators For No-tillage Sitesmentioning
confidence: 99%
“…Tropical soils, especially those under Brazilian Savannah areas, are typically acid, highly weathered, with low nutrient availability and high exchangeable acidity (Al3+) (Fageria, 2001;Gonçalves Jr. et al, 2014;Bojórquez-Quintal et al, 2017;Esper Neto et al, 2019). Therefore, to mantain high yield and grain quality, a routine of soil fertilization and amendment for mitigation of the aluminum toxicity and low pH is crucial (Fageria et al, 2014).…”
Section: Introductionmentioning
confidence: 99%